Genome-Wide Association Studies of Salt-Alkali Tolerance at Seedling and Mature Stages in Brassica napus - Zhang, Guofang; Peng, Yan; Zhou, Jinzhi; Tan, Zengdong; Jin, Cheng; Fang, Shuai; Zhong, Shengzhu; Jin, Cunwang; Wang, Ruizhen; Wen, Xiaoliang; Li, Binrui; Lu, Shaoping; et al. (Frontiers in Plant Science, 2022)
Most plants are sensitive to salt-alkali stress and the degree of tolerance to salt-alkali stress varies from different species and varieties. In order to explore the salt-alkali stress adaptability of Brassica napus, we collected the phenotypic data of 505 B. napus accessions at seedling and mature stages under control, low and high salt-alkali soil stress conditions in Inner Mongolia of China. 6 resistant and 5 sensitive materials, respectively, have been identified both in Inner Mongolia and Xinjiang Uygur Autonomous Region of China. Genome-wide association studies (GWAS) for 15 absolute values and 10 tolerance coefficients (TCs) of growth and agronomic traits were applied to investigate the genetic basis of salt-alkali tolerance of B. napus. We finally mapped 9 significant QTLs related to salt-alkali stress response and predicted 20 candidate genes related to salt-alkali stress tolerance. Some important candidate genes, including BnABA4, BnBBX14, BnVTI12, BnPYL8 and BnCRR1, were identified by combining sequence variation annotation and expression differences. The identified valuable loci and germplasms could be useful for breeding salt-alkali-tolerant B. napus varieties. This study laid a foundation for understanding molecular mechanism of salt-alkali stress adaptation and provides rich genetic resources for the large-scale production of B. napus on salt-alkali land in the future.